2022
DOI: 10.3390/jpm12111819
|View full text |Cite
|
Sign up to set email alerts
|

NTRK Gene Fusions in Solid Tumors and TRK Inhibitors: A Systematic Review of Case Reports and Case Series

Abstract: The approval of larotrectinib and entrectinib for cancer patients harboring an NTRK gene fusion has represented a milestone in the era of “histology-agnostic” drugs. Among the clinical trials that led to the approval of these two drugs, most of the enrolled patients were affected by soft tissue sarcomas, lung, and salivary gland cancer. However, as next-generation sequencing assays are increasingly available in the clinical setting, health care professionals may be able to detect NTRK gene fusions in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…185 Head and neck secretory carcinomas have shown response to TRK targeted therapies, [186][187][188] such that the diagnosis of secretory carcinoma in the lung may have implications for predictive biomarker testing and treatment. 189 The bland nuclear features and granularappearing cytoplasm of secretory carcinoma can give it an appearance similar to AciCC. 21,22,190 Positive mammaglobin immunostaining, the presence of mucicarmine-positive secretory material, and negative PAS staining can distinguish secretory carcinoma from AciCC.…”
Section: Sox10mentioning
confidence: 99%
See 1 more Smart Citation
“…185 Head and neck secretory carcinomas have shown response to TRK targeted therapies, [186][187][188] such that the diagnosis of secretory carcinoma in the lung may have implications for predictive biomarker testing and treatment. 189 The bland nuclear features and granularappearing cytoplasm of secretory carcinoma can give it an appearance similar to AciCC. 21,22,190 Positive mammaglobin immunostaining, the presence of mucicarmine-positive secretory material, and negative PAS staining can distinguish secretory carcinoma from AciCC.…”
Section: Sox10mentioning
confidence: 99%
“…Similarly, approximately 90% of head and neck secretory carcinomas harbour ETV6::NTRK fusions, 184 with a minority showing other fusions that often, but not always, involve ETV6 185 . Head and neck secretory carcinomas have shown response to TRK targeted therapies, 186–188 such that the diagnosis of secretory carcinoma in the lung may have implications for predictive biomarker testing and treatment 189 …”
Section: Rare or Newly Recognized Primary Pulmonary Salivary Gland‐ty...mentioning
confidence: 99%
“…The role of neutrophic thyrosine receptor kinase (NTRK) in GC was assessed in several studies, but it was suggested that the role is marginal as the occurrence of NTRK fusion in GC is very rare [86][87][88]. In spite of this, there is entrectinib, which has anti-cancer activity in GC cells with NTRK overexpression.…”
Section: Other Molecular Biomarkers Of Gcmentioning
confidence: 99%
“…Additionally, PDGFR inhibitors target gastrointestinal tumors, glioblastomas, sarcomas, leukemias, and dermatofibrosarcoma protuberans [113]. TRK is encoded by the NTRK gene family (NTRK1, NTRK2, and NTRK3) [114]. This proto-oncogene is responsible for cancer cell transformation, tumor cell proliferation, migration, and invasion.…”
Section: Protein Receptor Kinase/protein Kinasementioning
confidence: 99%